The spirit of despotism : invasions of privacy in the 1790s - Barrell, John (OUP E-Books., 2006)
How was the social and cultural life of Britain affected by the fear that the French Revolution would spread across the channel? In his brilliant new book, John Barrell argues that the fear of revolution produced a culture of surveillance and suspicion which penetrated every aspect of private life. The Spirit of Despotism shows how the culture of suspicion affected how people spoke and behaved in London coffee-houses; how it influenced attitudes to the king's behaviour on. holiday; how it infiltrated the country cottage, previously idealised as haven of peace and retirement; and how it influen.